The importance of lymph node retrieval and lymph node ratio following preoperative chemoradiation of rectal cancer. (30th July 2013) - La Torre, M.; Mazzuca, F.; Ferri, M.; Mari, F. S.; Botticelli, A.; Pilozzi, E.; Lorenzon, L.; Osti, M. F.; Marchetti, P.; Enrici, R. M.; Ziparo, V.
Abstract Aim Preoperative chemoradiation (CRT) for rectal cancer decreases the number of examined lymph nodes (NELN) found in the resected specimen. However, the prognostic role of lymph node evaluation including overall numbers and the lymph node ratio (LNR) in patients having preoperative CRT have not yet been defined. The study has assessed the influence of CRT on the NELN and on lymph node number and LNR on the survival of patients with rectal cancer. Method Between 2003 and 2011, 508 patients with nonmetastatic rectal cancer underwent mesorectal excision. Of these 123 (24.2%) received preoperative CRT. Univariate and multivariate analysis was performed to define the role of NELN and LNR as prognostic indicators of survival. Results Neoadjuvant CRT significantly reduced the NELN (P < 0.0001). Disease‐free survival (DFS) and overall survival (OS) of patients with fewer or more than 12 nodes retrieved did not differ statistically. Node‐negative patients with six or fewer lymph nodes were significantly associated with a poor DFS and OS on univariate analysis (P = 0.03 and P = 0.03). LNR significantly influenced the DFS and OS on multivariate analysis [DFS, P = 0.0473, hazard ratio (HR) 2.4980, 95% confidence interval (CI) 1.2631–9.4097; OS, P = 0.0419, HR 1.1820, 95% CI 1.1812–10, 710]. Conclusion The cut‐off of 12 lymph nodes does not influence survival and should not be considered for cancer‐specific prediction of patients having neoadjuvant CRT. In contrast LNR is an independent prognostic predictor of DFS and OS in such patients.